2016
DOI: 10.1007/s10815-016-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between follicular fluid high density lipoprotein particle components and embryo quality among in vitro fertilization patients

Abstract: Purpose Follicular redox balance is likely to be important for embryo quality during in vitro fertilization (IVF), and the anti-oxidative high desity lipoprotein (HDL) particle is the sole lipoprotein measured in follicular fluid (FF). Therefore, we investigated FF HDL particle components as predictors of embryo quality during IVF. Methods Two research follicles collected from each participant were individually tracked, and 103 women having at least one developed embryo were included in the analysis. Concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…In humans, smaller HDL particles exhibit higher antioxidant potential than larger HDL particles (Nobecourt et al, ). Additionally, an association between the presence of larger and medium HDL particles in FF with decreased embryo quality was observed (Kim et al, ). The source of HDL‐P used in this study was human plasma, which would indicate that average particle size may be larger than HDL observed in FF, as only smaller HDL particles (HDL 3 ) are present in FF due to the follicular membrane permeability (Shalgi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, smaller HDL particles exhibit higher antioxidant potential than larger HDL particles (Nobecourt et al, ). Additionally, an association between the presence of larger and medium HDL particles in FF with decreased embryo quality was observed (Kim et al, ). The source of HDL‐P used in this study was human plasma, which would indicate that average particle size may be larger than HDL observed in FF, as only smaller HDL particles (HDL 3 ) are present in FF due to the follicular membrane permeability (Shalgi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The source of HDL‐P used in this study was human plasma, which would indicate that average particle size may be larger than HDL observed in FF, as only smaller HDL particles (HDL 3 ) are present in FF due to the follicular membrane permeability (Shalgi et al, ). Furthermore, Kim et al () found 15 different compounds linked to the HDL particle and 26 different HDL particle sizes, demonstrating the complexity of the HDL particle, which reflects on its complex functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human mechanistic studies relating individual circulating lipoproteins and fertility are scarce . There is extensive information characterising concentrations of lipoproteins in the oocyte, however, revealing that HDL‐C is the most abundant lipoprotein in follicular fluid, and appears to have a most influential role, implicated in embryo development and quality . Triglycerides are found in lower quantities in follicular fluid and LDL‐C is negligible .…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is known to be essential for the process of steroidogenesis, and serum free cholesterol concentrations have been associated with fecundity in both sexes [11, 15]. HDL cholesterol is, along with Apolipoprotein b (Apo b) [17, 18], the predominant lipoprotein in ovarian follicles, and is associated with embryo quality and fertility treatment outcomes [16, 19]. Human studies have reported appreciably higher clinical pregnancy rate and number of top-quality embryos in high Apo b patients undergoing fertility treatment, compared with low Apo b patients, even after exclusion of ovarian-related disorders [17].…”
Section: Introductionmentioning
confidence: 99%